Retracted: Comparative evaluation of post-operative analgesic effects of intraperitoneal levobupivacaine plus fentanyl and levobupivacaine plus tramadol in patients undergoing laparoscopic cholecystectomy - Katoch, Madan lal; Kour, Loveleen (International Journal of Clinical Trials, 2020)
The article "Comparative evaluation of post-operative analgesic effects of intraperitoneal levobupivacaine plus fentanyl and levobupivacaine plus tramadol in patients undergoing laparoscopic cholecystectomy" is retracted by the Editor-in-Chief, due to violation of the policies and practices of International Journal of Clinical Trials. The article is retracted due to dispute in authorship.